Essential commodities prices, availability, and market actors’ perceptions: October 2025 - Rakhy, Tariq; Abushama, Hala; Mohamed, Shima; Nigus, Halefom Yigzaw; Siddig, Khalid (International Food Policy Research Institute, 2025)
Sudan’s markets in October 2025 showed relative stability with several commodities experiencing improved availability and quality. Wheat and wheat flour prices declined, while sorghum, millet, vegetables, lentils, meat, oilseeds, and sugar showed mixed but generally stable trends. Fuel prices fell early in the month before stabilizing, and fertilizer prices remained steady with better availability.